O impacto dos benefícios e do desemprego sobre os salários do trabalhador no Brasil - Wendhausen, Enimar Jerônimo (2019)
This thesis contributes to the academic literature in the analysis of the impact of benefits and unemployment on the salaries of Brazilian workers. The first part of the study examines the extent to which the benefits offered to workers influence the wage differential in the labor market, also highlighting the factors responsible for the wage differential of these workers and the measurement of the differentials of income from work between the five regions of the country. The pseudo panel technique (almost panel) and the Oaxaca and Blinder decomposition method are adopted. The functional form of the regressions is based on the Mincer equation, formulated from the Human Capital Theory. The data used are part of the National Survey of Household Sample (PNAD) of the Brazilian Institute of Geography and Statistics (IBGE), covering the period from 1995 to 2015. The benefits (aids) considered in the study are food, education, housing, health and transportation. The results show that, although the workers benefited with certain aids can receive the benefit linked to factors such as human capital, the productive attributes were not presented as the only factors responsible for the explanation of the granting of benefits to workers, as well as by the impact on the wage differential. That is, the results also show that aspects related to the regional particularities of the market among other aspects also influence wage differentials. The second part analyzes the impact of unemployment on wages from the consideration of data on the formal education of workers in Brazil. In this way, the marginal contribution of variables (education, unemployment, interaction between years of schooling and unemployment, and interaction between years of experience and unemployment) in wages is analyzed. The empirical investigation of the study is based on the methodologies of estimation of the panels of Fixed Effect (FE) and Random Effect (RE), as well as the dynamic panel Arellano and Bond, using PNAD microdata and macroeconomic data. In the second part, the results indicate positive impacts of schooling and interactive variables on wages, despite the observed unemployment in the labor market. It is possible to say that, in this case, the years of schooling and the experience of the workers have been able to somewhat attenuate the effect of unemployment on wages.